Increasing Domestic Procurement by the Mining Sector in Central Asia - Esteves, Ana Maria; Ogorodnikova, Vera; Putz, Cyrille; Coyne, Bruce (World Bank, Washington, DC, 2014)
This study has focused on the third factor, specifically, the creation of local benefits through supplier linkages. The World Bank commissioned a pilot study to inform the nature and scale of potential support to the three Central Asian countries, with the goal of mining-related domestic procurement serving as an instrument to increase employment and industrialization. This document presents on the findings of the study, undertaken by Community Insights Group during the period May to July 2013. The report starts with an overview of current global trends with respect to domestic procurement by mining operations. Sections 3-5 describe the situation in Kazakhstan, Kyrgyzstan and Tajikistan with regard to company legal obligations and practices, and government programs and capacities to support domestic SMEs supplying the mining industry. The situation analysis is followed by a summary of case studies (Section 6) undertaken with mining operations to determine their current procurement needs, current local procurement efforts, and barriers to increasing procurement. The case studies also included the perspective of local suppliers and potential local suppliers. The report closes with a set of recommendations for World Bank consideration, to guide future interventions.